Can EAT be an INOCA goalkeeper - Shan, Tong; Shuwen, Zheng; Hengbin, Wu; Min, Zeng (Frontiers in Endocrinology, 2023)
Ischemia with non-obstructive coronary artery (INOCA) is a blind spot of coronary artery disease (CAD). Such patients are often reassured but offered no specific care, that lead to a heightened risk of adverse cerebrovascular disease (CVD) outcomes. Epicardial adipose tissue (EAT) is proven to correlate independently with CAD and its severity, but it is unknown whether EAT is a specific and sensitive indicator of INOCA. This review focuses on the INOCA epidemiology and related factors, as well as the association between EAT.